Optimal Operation of Microgrid Considering Photovoltaic,Storage and Turbine - XIANG Hongwei; CHANG Xiqiang; L Menglin; XING Zhanli; WANG Han (Journal of Harbin University of Science and Technology)
Considering the time series correlation between photovoltaic and load, the generalized load is introduced. K-means clustering is used to obtain the typical scenarios of microgrid operation and the probability of each scenario. The optimization model considers the comprehensive operation and maintenance cost as the objective function. Constraints include power balance constraints, etc. The improved particle swarm optimization algorithm is used to solve the problem. The charging and discharging strategies of energy storage and electric vehicle are obtained which is under grid connected and island operation modes. Finally, an example of a lowvoltage microgrid is given to verify the effectiveness of the proposed method and model.